Dihydropyrrolones as bacterial quorum sensing inhibitors - Almohaywi, Basmah (2020)
Bacteria regulate their pathogenicity and biofilm formation through quorum sensing (QS), which is an intercellular communication system mediated by the binding of signaling molecules to QS receptors such as LasR. In this study, a range of dihydropyrrolone (DHP) analogues were synthesized via the lactone-lactam conversion of lactone intermediates. The synthesized compounds were tested for their ability to inhibit QS, biofilm formation and bacterial growth of Pseudomonas aeruginosa. The compounds were also docked into a LasR crystal structure to rationalize the observed structure-activity relationships. The most active compound identified in this study was compound 9i, which showed 63.1% QS inhibition of at 31.25 µM and 60% biofilm reduction at 250 µM with only moderate toxicity towards bacterial cell growth.